Cities of the world regional patterns and urban environments - Brunn, Stanley D.; Graybill, Jessica K.; Hays-Mitchell, Maureen; Zeigler, Donald J. (Rowman & Littlefield, 2016)
The contributors explore how water affects cities and how cities affect water--from glacier loss to growing aridity, sea-level rise, increased flooding, potable water scarcity, and beyond. Vignettes of key cities give the reader a vivid understanding of daily life and the "spirit of place.